An initial study on the impression creep behaviour of stir-cast GNP reinforced AA6061 composite (AMMC). Issue 1 (1st July 2022) - Khokhar, Ostin; Khajuria, Akhil; Bedi, Raman
Abstract: Impression creep testing technique is used to screen out creep behaviour of materials as it is relatively faster method, requires small volume of the specimen, and is relatively material non-invasive technique when compared to conventional uniaxial tensile creep test method. This technique also possesses the benefit of maintaining constant stress throughout the experiment because a flat cylindrical indenter is used to apply load on the specimen. Owing to commercial unavailability of the materials under development such as metal matrix composites (MMC), the impression creep testing approach for such materials becomes a best method. In present work, creep behaviour of stir-cast graphene nanoplatelets (GNP) reinforced AA6061 composite (AMMC) is studied by using impression creep tests. The AMMC was prepared by adding GNPs in AA6061 through stir casting process by melting the alloy up to 1073 K. The impression creep experimentation included stress levels of 140 MPa, 170 MPa, and 200 MPa at a temperature of 573 K, 603 K and 633 K. The tests were conducted at constant stress by varying the temperature and vice-versa in vacuum. Two distinct regions i.e., primary and secondary/steady-state were observed and minimum creep strain rate was obtained in steady-state region. Tertiary region was absent, since the load/stress applied was compressive. During the experiment, depth of indentation of 0.03 mm to 0.14 mm was produced in the specimen. The microstructure of the composite has been analyzed using optical microscope and scanning electron microscope (SEM) to correlate with impression creep behaviour of the studied materials.